PEMBELAJARAN MENULIS PUISI BERORIENTASI MAJAS DENGAN MENGGUNAKAN METODE CREATIVE LEARNING PADA SISWA KELAS X SMA AL-HIDAYAH CIPARAY KABUPATEN BANDUNG - Nugraha, Eggie; Priatna, Asep (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2017)
Today the development of Indonesian literature is growing rapidly. One effort to encourage the advancement of Indonesian literature is to improve the teaching of literary appreciation at every level of school. In order for students interested in learning to write poetry so as to develop creations and imagination. Based on the above background, the author is interested in conducting research on "Writing Poetry Oriented Learning Method Using Majas with Creative Learning in Class X SMA Al-Hidayah Ciparay. This study aims to determine the success of the author in implementing learning to write poetry oriented figure of speech with a method of creative learning in class X SMA Al-Hidayah Ciparay, determine the ability of class X SMA Al-Hidayah Ciparay in writing poetry oriented figure of speech with a method of creative learning and knowing ketefektipan creative learning methods used in learning to write poetry oriented figure of speech in class X SMA Al-Hidayah Ciparay. Writer formulated hypotheses are: (1) The authors were able to carry out the figure of speech-oriented learning to write poetry using creative methods of learning in class X SMA Al-Hidayah Ciparay; (2) Grade X SMA Al-Hidayah Ciparay able to write poetry using a figure of speech-oriented creative methods of learning; (3) The method of creative learning is effectively used in learning to write poetry using a figure of speech-oriented creative methods of learning in class X SMA Al-Hidayah Ciparay. Research method that writer use is quasi-experiment method with research technique of literature study, trial, test and analysis.